What's in a Name? Effects of Alternative Forms of Addressing Households on Response Rates and Data Quality in an Address-based Mail Survey. Issue 1 (February 2019) - Dykema, Jennifer; Assad, Nadia; Sanchez-Diettert, Griselle; Elver, Kelly; Stevenson, John
Best practices in mail survey design advise personalizing correspondence, but most research predates the use of address-based sampling (ABS) in which a householder's name either cannot be matched to an address or may be matched incorrectly. Further, recent evidence casts doubt on the effectiveness of personalization. The current study examines the impact of using a personalized versus a generic salutation on response rates and data quality in an ABS mail survey of the general population. A sample of 2, 000 household addresses in Wisconsin was randomly selected from the U.S. Postal Service Delivery Sequence File. For households in the personalized salutation group, all materials used the surname of the household; cases in the generic salutation group referred to the state conducting the survey. While personalization was not related to response rates, it was associated with higher levels of item nonresponse. Findings support current recommendations not to use names in ABS mail surveys.